Predictors of Impact of Vaginal Symptoms in Postmenopausal Women - Hunter, Mary M. (Menopause, 2016)
OBJECTIVE: To identify factors associated with greater impact of vaginal symptoms on functioning and well-being in postmenopausal women. METHODS: Postmenopausal women who reported vaginal dryness, itching, irritation, or pain with sexual activity completed the multidimensional Day-to-day Impact of Vaginal Aging (DIVA) questionnaire and underwent assessment of multiple socio-demographic and clinical factors having the potential to influence the impact of vaginal symptoms. Multivariable linear regression analyses examined relationships between selected participant characteristics and DIVA scale scores assessing symptom impact on activities of daily living, emotional well-being, self-concept/body image, and sexual functioning. RESULTS: Among the 745 symptomatic participants, mean age was 56 (±9) years, and 66% were racial/ethnic minorities. Women with comorbid depression reported greater impact of vaginal symptoms on all dimensions of functioning and well-being measured by DIVA (11%–22% estimated increase in impact scores associated with each 3-point increase in Hospital and Anxiety Depression Scale scores). Women with urinary incontinence also reported greater impact of vaginal symptoms on activities of daily living, emotional well-being, and self-concept/body image (27%–37% estimated increase in impact scores). Age, partner status, sexual activity frequency, general health, and body mass index also predicted greater impact in at least one domain. CONCLUSIONS: Findings suggest that special efforts should be made to identify and treat vaginal symptoms in postmenopausal women known to have depression or urinary incontinence, as these women may experience greater impact of vaginal symptoms on multiple domains of functioning and quality of life.